MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR GEOGRAFI MATERI ATMOSFER MELALUI MODEL PEMBELAJARAN JIGSAW KELAS X IIS 2 SMA NEGERI 3 KUALA KAPUAS TAHUN PELAJARAN 2014/2015 - I Nyoman Sudiana (JURNAL SOCIUS, 2015)
This study aims to improve students learning activities and learning outcomes of Geography through jigsaw model in class X IIS 2 SMA Negeri 3 Kuala Kapuas. The application of jigsaw model in class X IIS 2 SMA Negeri 3 Kuala Kapuas was supposed to have positive impact on building learning activities and learning outcomes of students in the process of learning Geography, in particular ‘atmosphere’ materials.This research is a classroom action research (CAR). The design of study used the model proposed by Suharsimi consisting of 4 stages: planning, implementation, observation, and reflection. The subjects were students of class X IIS 2 SMA Negeri 3 Kuala Kapuas with a total of 18 students. The implementation of action of each cycle was done using Jigsaw model.The method used in data collection was observation. The research instrument used was in the form of observation sheet. Observation method was conducted to observe students activities during the course. Data were analyzed using qualitative descriptive technique. Indicators of success in this study were normative criteria, i.e. when there is an increase after the action. In this research,  the teacher applied Jigsaw model, grouping groups of origins, groups of experts, discussion and presentation.The results of this study concluded that: (1) student activities increased from 72% of less active category to 94.6% of active category, (2) student learning outcomes increased from 74.66% to 80.55%. Thus, the application of jigsaw model can improve student activities and student learning outcomes of Geography in class X IIS 2 SMA Negeri 3 Kuala Kapuas.Keywords:  Jigsaw model, student activities, learning outcomes, geography matter